The Effect of Consuming Sukari Date Palm Juice (Phoenix Dactylifera Extract) on Accelerating Early Mobilization in Postpartum Mothers from Day 1 to Day 3 in the Work Area of the Sikui Community Health Center (UPT) - Rima Miranti; Anik Purwati (STIKES Columbia Asia Medan, 2025)
Early mobilization is an important component of postpartum midwifery care to prevent complications, accelerate physical recovery, and improve maternal comfort after delivery. However, not all mothers are able to perform early mobilization optimally due to fatigue, pain, and decreased energy after delivery. Sukari date palm juice (Extractum Phoenix dactylifera) is known to contain simple carbohydrates, minerals, and bioactive compounds that have the potential to increase energy and accelerate maternal recovery. This study aims to analyze the effect of consuming Sukari date palm juice on accelerating early mobilization of postpartum mothers from day 1 to day 3 in the working area of ​​the Sikui Community Health Center (UPT). The study used a quasi-experimental design with a pretest–posttest control group approach. The study sample consisted of 30 postpartum mothers divided into an intervention group (n=15) and a control group (n=15). Early mobilization ability was assessed based on the time the mother was able to sit, stand, and walk. The results showed that postpartum mothers in the intervention group experienced a significant acceleration in early mobilization compared to the control group, particularly in walking ability, with a time difference of up to 8–12 hours faster. The results of the Mann–Whitney statistical test showed a significant effect of date palm juice consumption on the acceleration of early mobilization (p < 0.001). Thus, Sukari date palm juice has been proven to be effective in accelerating early mobilization and can be recommended as a supporting nutritional intervention in postpartum midwifery care.